Strains of Staphylococcus and Bacillus Isolated from Traditional Sausages as Producers of Biogenic Amines - Bermúdez, Roberto; Lorenzo, Jose M.; Fonseca, Sonia; Franco, Inmaculada; Carballo, Javier (Frontiers in Microbiology, 2012)
Histidine, lysine, ornithine and tyrosine decarboxylase activities were tested in 38 strains of Staphylococcus (15 of Staph. equorum, 11 of Staph. epidermidis, 7 of Staph. saprophyticus, and 5 of Staph. pasteuri) and 19 strains of Bacillus (13 of B. subtilis and 6 of B. amyloliquefaciens) isolated from two Spanish traditional sausage varieties. The four decarboxylase activities were present in most of the strains studied, but some variability was observed between strains within each microbial species. Accumulation of putrescine and cadaverine was assessed in the culture media of the strains that displayed ornithine and lysine decarboxylase activities. The aminogenic potential of the strains was low, with amounts accumulated lower than 25 mg/L for the putrescine and than 5 mg/L for the cadaverine, with the exception of a strain of Staph. equorum that produced 1415 mg/L of putrescine, and of a strain of Staph. epidermidis that accumulated 977 mg/L of putrescine and 36 mg/L of cadaverine.